COVID-19 and athletes: Endurance sport and activity resilience study—CAESAR study - Sliz, D.; Wiecha, S.; Ulaszewska K.; Gasior, J. S.; Lewandowski, M.; Kasiak P. S.; Mamcarz, A. (Frontiers in Physiology, 2022)
Background: The COVID-19 pandemic and imposed restrictions influenced athletic societies, although current knowledge about mild COVID-19 consequences on cardiopulmonary and physiologic parameters remains inconclusive. This study aimed to assess the impact of mild COVID-19 inflection on cardiopulmonary exercise test (CPET) performance among endurance athletes (EA) with varied fitness level.